ANALISIS PERBANDINGAN ABNORMAL RETURN SAHAM SEBELUM DAN SESUDAH STOCK SPLIT - Alvina Damayanti; Rosida Dwi Ayuningtyas; Sri Retnoningsih (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
Thisstudy aims to analyze whether there is a significant abnormal return before and after the stock split and the difference in abnormal returns before and after the stock split. The analysis method used in this study is the Wilcoxon Signed Ranked Test test method. The population in this study is all companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The samples used in this study were 17 companies. The Wilcoxon Signed Ranked Test on the significance of abnormal returns found that there was no abnormal significance of returns before and after stock split with significance > 0.05. The results of the Wilcoxon Signed Ranked Test on the difference in abnormal returns before and after the stock split found that there was nodifference in abnormal returns before and after the stock split with a significance result of 0.16 > 0.05.